VD_FINDINFO Arrêt / 2022 / 796 vom 14. November 2022 - VD Tribunal cantonal (2022)
CALCUL, RESTITUTIONEN GÉNÉRAL, ADMISSION DE LA DEMANDE, CONDITION DU DROIT À LA PRESTATION D'ASSURANCE | 10 LPC, 16 OPC-AVS/AI